Training on the Development of Mindfulness-Based Guidance and Counseling Media to Enhance School Counselors’ Competence in Supporting Student Well-Being - Yunita Dwi Setyoningsih; Agus Setiawan; Agung Prasetyo (STKIP Singkawang, 2026)
This community service program aimed to improve guidance and counseling teachers’ competence in developing mindfulness-based counseling media to support student well-being. The program was conducted on May 12, 2026, at SMA N 1 Rembang in collaboration with the Senior High School/Madrasah Aliyah Guidance and Counseling Teachers’ Association of Rembang Regency, with funding from LPPM Universitas Persatuan Guru Republik Indonesia Semarang. A total of 51 teachers completed the pretest, while 46 completed the posttest. The training included interactive lectures, demonstrations, media design practice, simulations, discussions, and evaluation. Data were analyzed descriptively using means, percentages, categories, and open-response review. The pretest showed that participants’ initial competence was moderate to high, with a mean score of 3.39 or 67.70%. After training, the posttest score increased to 4.34 or 86.89%, categorized as very high. In the 17 comparable items, the score increased from 3.39 to 4.31. The highest improvement was found in confidence and implementation evaluation. This program indicates that practice-based training can strengthen school counselors’ competence in developing mindfulness-based media.Pelatihan Pengembangan Media BK Berbasis Mindfulness untuk Meningkatkan Kompetensi Guru Bimbingan dan Konseling dalam Mendukung Well-Being SiswaABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kompetensi guru Bimbingan dan Konseling dalam mengembangkan media BK berbasis mindfulness untuk mendukung well-being siswa. Kegiatan dilaksanakan pada 12 Mei 2026 di SMA N 1 Rembang bersama mitra MGBK SMA/MA Kabupaten Rembang, dengan dukungan pendanaan LPPM Universitas Persatuan Guru Republik Indonesia Semarang. Peserta yang mengisi pretest berjumlah 51 guru BK, sedangkan posttest diisi oleh 46 guru BK. Metode pelaksanaan meliputi ceramah interaktif, demonstrasi, praktik perancangan media, simulasi, diskusi, dan evaluasi. Data dianalisis secara deskriptif melalui rerata, persentase, kategori, serta telaah respons terbuka. Hasil pretest menunjukkan kompetensi awal peserta berada pada kategori sedang menuju tinggi dengan rerata 3,39 atau 67,70%. Setelah pelatihan, skor posttest meningkat menjadi 4,34 atau 86,89% pada kategori sangat tinggi. Pada 17 butir yang sama, skor meningkat dari 3,39 menjadi 4,31. Peningkatan terbesar terjadi pada kepercayaan diri dan evaluasi pelaksanaan. Kegiatan ini menunjukkan bahwa pelatihan berbasis praktik dapat memperkuat kompetensi guru BK dalam mengembangkan media mindfulness untuk mendukung well-being siswa.Kata Kunci :guru BK; media BK; mindfulness; well-being siswa